Two-ligand priming mechanism for potentiated phosphoinositide synthesis is an evolutionarily conserved feature of Sec14-like phosphatidylinositol and phosphatidylcholine exchange proteins - Huang, Jin; Ghosh, Ratna; Tripathi, Ashutosh; Lönnfors, Max; Somerharju, Pentti; Bankaitis, Vytas A. (Molecular biology of the cell, 2016)
Lipid signaling, particularly phosphoinositide signaling, plays a key role in regulating the extreme polarized membrane growth that drives root hair development in plants. The Arabidopsis AtSFH1 gene encodes a two-domain protein with an amino-terminal Sec14-like phosphatidylinositol transfer protein (PITP) domain linked to a carboxy-terminal nodulin domain. AtSfh1 is critical for promoting the spatially highly organized phosphatidylinositol-4,5-bisphosphate signaling program required for establishment and maintenance of polarized root hair growth. Here we demonstrate that, like the yeast Sec14, the AtSfh1 PITP domain requires both its phosphatidylinositol (PtdIns)- and phosphatidylcholine (PtdCho)-binding properties to stimulate PtdIns-4-phosphate [PtdIns(4)P] synthesis. Moreover, we show that both phospholipid-binding activities are essential for AtSfh1 activity in supporting polarized root hair growth. Finally, we report genetic and biochemical evidence that the two-ligand mechanism for potentiation of PtdIns 4-OH kinase activity is a broadly conserved feature of plant Sec14-nodulin proteins, and that this strategy appeared only late in plant evolution. Taken together, the data indicate that the PtdIns/PtdCho-exchange mechanism for stimulated PtdIns(4)P synthesis either arose independently during evolution in yeast and in higher plants, or a suitable genetic module was introduced to higher plants from a fungal source and subsequently exploited by them.